Evaluation of Milk Characteristics of Karadi Sheep Breed in Halabja Province, Kurdistan Region of Iraq - Karym, Chnoor Mhamad; AL-Barzinji, Yousif M. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
In the Kurdistan region, sheep play a pivotal role as the most significant farm animals, with lamb sales constituting a major portion of the income. In present study data was collected from commercial Karadi ewes flock located in Chawg village, Halabja province, Kurdistan Region of Iraq. A total of 163 ewes were utilized to investigate the impact of various factors on daily milk yield (DMY), total milk yield (TMY), lactation period (LP) and the percentages of total solid (TS), fat, protein and lactose. The investigation also sought to determine correlations among these parameters. The least square mean ± SE of DMY, TMY, LP and the percentages of TS, fat, protein and lactose were 613.5±90.06g/ewe/day, 67.05±11.8kg/ewe, 107.8±11.14day/ewe and 16.41±1.84%, 5.79±0.69%, 5.43±0.64% and 4.28±0.51%, respectively. It is evident that all fixed effects, with the exception of the type of birth, wield a significant influence (P≤0.05) on both milk production and composition. Notably, a substantial positive correlation (p≤0.01) was observed between total solid percentages and the percentages of fat, protein and lactose. The BLUP values for TMY were ranged from -60.64 kg/ewe to 1 kg/ewe, while the MPPA value for TMY were ranged from 57.73092 to 78.83427. The wide range of BLUP values and the MPPA values ​​for TMY indicate the presence of significant genetic variation among the Karadi ewes under study, where selection can play an important role in increasing productivity and the genetic and economic gain to the breeder in next generation and increasing genetic and productive ability of Karadi sheep in the Kurdistan region of Iraq.